Uncertainty treatment using paraconsistent logic introducing paraconsistent artificial neural networks - Silva Filho, João Inácio da (Frontiers in artificial intelligence and applications Knowledge-based intelligent engineering systems, 2010)
This book aggregates much of this research, from 1999 up to the present. Organized to facilitate an understanding of the theory and the development of the applied methods, Uncertainty Treatment Using Praconsistent Logic presents the material in a sequential fashion and is divided into three parts.